Case report of intraventricular schwannoma. (2nd January 2019) - Razak, Adam A.; O'Reilly, Gerry M.; Highley, Robin; Hussain, Muhammad M.
Abstract: We describe the case of a 52 year old male presenting with subacute headache. Cranial imaging suggested haemorrhage into a parietal, partially intraventricular, space occupying lesion. The radiology was interpreted to be most consistent with a glioblastoma. The lesion was near totally resected. The histopathology was a WHO grade 1 schwannoma.